Trademarks as an indicator of innovation and industrial change - Sandro Mendonça; Tiago Santos Pereira; Manuel Mira Godinho (Scuola Superiore Sant'Anna, Laboratory of Economics and Management (LEM), 2004)
As innovation becomes an ever more central issue for the development of firms and world economies, so the need for improved assessments of innovative performance grows more urgent. This paper suggests that trademark analysis can contribute in capturing relevant aspects of innovation phenomena and the process of industrial change. We propose trademarks as a complementary indicator in the portfolio of available empirical tools of innovation studies and industrial dynamics. Our empirical exploration is based on a study of Community Trade Marks, an intellectual property right granted in the European Union, and draws on recent research on trademarking trends in Portugal. Quantitative as well as qualitative data, including survey data from a representative sample of Portuguese manufacturing and services firms, are used to identify the advantages and limitations of this indicator.
Keywords: 330; indicators; trademarks; innovation; industrial dynamics; Wirtschaftsindikator; Handelsmarke; Innovation; Strukturwandel; Theorie